Profile of Students' Creative Thinking Ability Reviewed from Self-Confidence - Kartika Rusiyaningsih; Saudah Saudah; Gunawan Gunawan; Fitrianto Eko Subekti (STKIP Singkawang, 2025)
Creative thinking skills are students' ability to find ways or solutions that are unusual, unique, and have never been found by others in solving problems. This study aims to describe the ability to think creatively from the perspective of students' confidence. The research method used was qualitative descriptive, with data collection techniques through questionnaires, tests, and interviews. Questionnaires were used to divide the categories of student confidence, written tests were used to determine creative thinking skills in solving problems, and interviews were used to dig deep into information to obtain information related to problem solving. The subject of this study was sixth-grade VIII students of SMP N 1 Pekuncen. Subjects were grouped into three categories of confidence, namely high, medium, and low, based on the results of the questionnaire, using the purposive sampling technique; two people were taken as subjects in each category. The material used was a two-variable linear equation system. Data analysis techniques included data reduction, data presentation, and a conclusion drawn. The results of the study explained that (1) students with high categories were able to find solutions appropriately and could write down many ways to solve problems; (2) students in the medium confidence category could write down many ways to solve problems but couldnot find the right solution; (3) students with low confidence categories were not able to find the right solution and were unable to write down many ways to solve problems.